Tārīẖ-i Anjuman - Šahzād Manẓar (Anjuman-i Taraqqī-i Urdū Pākistān, 2002)
Historical and critical study of Anjuman Taraqqī-i Urdū Pākistān, Urdu literary society in Pakistan
In arab. Schrift, Urdu
Keywords: Urdu Literature